2022
DOI: 10.3390/ijerph192013350
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations of Ukrainian Migrants and Refugees in Poland in the Time of the Russia-Ukraine Conflict

Abstract: Background: In the face of a sudden influx of several million migrants and war refugees from Ukraine to other European countries, knowledge about the health of Ukrainian citizens becomes increasingly important. The aim of the study is to identify the main health problems of hospitalized Ukrainian citizens residing in Poland in the period from 2014 to June 2022. Methods: This study is based on hospitalization data of Ukrainian patients in Poland taken from the Nationwide General Hospital Morbidity Study. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“… 31 Moreover, Polish medical records in February–June 2022 listed 578 Ukrainian women and documented a high percentage of subjects hospitalized due to diseases related to pregnancy, childbirth, and the puerperium (228 [39%]). 32 This study pointed to a high risk of neonatal morbidity and mortality among immigrant Ukrainian women. Subsequently, securing the refugees’ rights for effective contraception and safe abortion may save their lives and improve family planning during and after the war.…”
Section: Sexual and Reproductive Healthmentioning
confidence: 77%
“… 31 Moreover, Polish medical records in February–June 2022 listed 578 Ukrainian women and documented a high percentage of subjects hospitalized due to diseases related to pregnancy, childbirth, and the puerperium (228 [39%]). 32 This study pointed to a high risk of neonatal morbidity and mortality among immigrant Ukrainian women. Subsequently, securing the refugees’ rights for effective contraception and safe abortion may save their lives and improve family planning during and after the war.…”
Section: Sexual and Reproductive Healthmentioning
confidence: 77%
“…Existing literature such as [35][36][37][38][39] focused on the specific domain of study to assess the impact of the RUW on the energy, gas (crude oil), food, healthcare, and stock markets, respectively, whereas our work highlights the generalized societal emotions and views of the RUW. Moreover, by complementing prior studies such as [40,41] we have chosen Twitter for this study to provide an automatic emotion classification framework by combining, NLP, TL, and ML altogether.…”
Section: Novelty and Contributionsmentioning
confidence: 99%
“…Understanding the health of Ukrainian residents is crucial in light of the rapid migration of several million migrants and war refugees from Ukraine into other European nations. In [38], the authors identified the major health issues by analyzing the nationwide general hospital morbidity data for Ukrainian residents who resided in Poland from 2014 to June 2022. At this time, diseases associated with pregnancy, childbirth, and puerperium were the most frequently reported primary causes of hospitalizations for adult women.…”
Section: Ruw and Global Impactmentioning
confidence: 99%
“…Between February 24 and June 30, 2022, there were 2230 reported hospitalizations of Ukrainian patients in Poland, which included 1494 children, 578 adult women, and 158 adult men [ 7 ]. Within the first 3 months of the onset of the conflict, 27 861 Ukrainian refugees, of whom 58% were children, received treatment in Polish healthcare facilities, mainly as outpatients [ 7 ]. In 2022, Poland had the highest total social and healthcare costs from accepting Ukrainian refugees, estimated at approximately 8.4 billion euros [ 8 ].…”
Section: Refugee Access To Healthcare In Polandmentioning
confidence: 99%